123 T and B lymphocyte senescence in parkinson's disease. Issue 12 (14th November 2019) - Jensen, Melanie; Scott, Kirsten; Camacho, Marta; Greenland, Julia; Kouli, Antonina; Wijeyekoon, Ruwani; Solim, Imtiaz; Barker, Roger; Williams-Gray, Caroline
Abstract : Introduction: Evidence suggests the immune system contributes to Parkinson's disease (PD) aetiopathogenesis and this represents a tractable target for disease-modifying therapy. As ageing is a risk factor for PD, it is relevant to investigate age-related immune changes (immunosenescence) in PD. Methods: Blood samples were collected from 20 early PD patients and 20 controls. T- and B-cell senescence subsets were identified using flow cytometric immunophenotyping. CMV/EBV serostatus was ascertained given its well-documented effect on immunosenescence. Results: CD4+ TEMRA cells, T-cell senescence markers, were reduced in PD cases versus controls (p=0.046). This was not driven by differences in age or CMV/EBV serostatus across groups. CMV positivity was associated with increased CD4+ TEMRA cells as expected in controls, but not in PD cases. Switched memory B-cells were lower in patients versus controls (p=0.040). No changes were observed in the CD8+ T-cell pool. Conclusions: These findings suggest that the senescent 'shift' induced by viral infection and ageing is atypical in PD. Reductions in senescent lymphocytes may favour the passage of activated lymphocytes across the blood brain barrier, promoting central inflammation and neurodegeneration. Pragmatically, this study shows that immune abnormalities occur in early-stage disease, adding urgency to the search for immune-modulating therapies in PD.